Algorithm-architecture matching for signal and image processing best papers from Design and Architectures for Signal and Image Processing 2007 & 2008 & 2009 - Gogniat, Guy.; SpringerLink (Online service). (Dordrecht, the Netherlands New York Springer, 2011)
Algorithm-Architecture Matching for Signal and Image Processing presents a collection of selected contributions from both industry and academia, addressing different aspects of Algorithm-Architecture Matching approach ranging from sensors to architectures design. The scope of this book reflects the diversity of potential algorithms, including signal, communication, image, video, 3D-Graphics implemented onto various architectures from FPGA to multiprocessor systems. Several synthesis and resource management techniques leveraging design optimizations are also described and applied to numerous algorithms.
Preface -- Part 1: Architectures for embedded applications -- Chapter 1: Architectures for image processing -- Chapter 2: Architectures for signal and telecommunication processing -- Part 2: Data acquisition and embedded systems -- Chapter 3: Sensors for data acquisition -- Chapter 4: Operators for embedded systems -- Chapter 5: Partial and dynamic reconfiguration for signal and image processing -- Part 3: Embedded systems design -- Chapter 6: RTOS for embedded systems -- Chapter 7: Scheduling of embedded systems -- Chapter 8: CAD tools for signal and image processing.
Electronic reproduction.
Keywords: Computer architecture; Computer algorithms; Signal processing; Image processing; Electronic books